New Dendrimers with Multi Arm 1,2,3-Thiadiazoles as a Nucleus - AL-SMADI, MOUSA (Asian Journal of Chemistry, 2010)
New dendrimers 1c-4c with multi-arm 1,2,3-thiadiazole systems 1a-4a have been prepared and characterized. Alkaline cleavage of 1a-4a led to the corresponding alkynethiolate 1b-4b, which were trapped by electrophiles such as Fréchet's[G-3]-Br to furnish the third-generation dendrimers. The advantage of the use of 1a-4a as nucleophilic core reagents lies in the linear alkyne groups that emanate from the benzene nucleus, thus allowing the construction of high molecular weight dendrimers.